2014
DOI: 10.1002/bip.22527
|View full text |Cite
|
Sign up to set email alerts
|

Development of high throughput screening assays and pilot screen for inhibitors of metalloproteases meprin α and β

Abstract: Zinc metalloproteinases meprin α and meprin β are implicated in a variety of diseases, such as fibrosis, inflammation and neurodegeneration, however, there are no selective small molecule inhibitors that would allow to study their role in these processes. To address this lack of molecular tools we have developed high throughput screening (HTS) assays to enable discovery of inhibitors of both meprin α and meprin β and screened a collection of well characterized pharmaceutical agents (LOPAC, n = 1,280 compounds)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…While this work was in progress, however, OuYang et al showed that it could induce HCC cell migration and invasion [ 14 ]. Interestingly, there are already available good meprin α inhibitors like actinonin [ 15 ] that can be used in vivo [ 16 – 18 ], and more specific inhibitors are currently under development [ 19 ], raising the hope that meprin α may become a clinically useful target.…”
Section: Introductionmentioning
confidence: 99%
“…While this work was in progress, however, OuYang et al showed that it could induce HCC cell migration and invasion [ 14 ]. Interestingly, there are already available good meprin α inhibitors like actinonin [ 15 ] that can be used in vivo [ 16 – 18 ], and more specific inhibitors are currently under development [ 19 ], raising the hope that meprin α may become a clinically useful target.…”
Section: Introductionmentioning
confidence: 99%
“…Assay miniaturization and optimization in 1,536 well plate format. The meprin α and meprin β assays, which utilize the substrates (Mca)-YVADAPK-(K-ε-Dnp) and (Mca)-EDEDED-(K-ε-Dnp), respectively, have been described previously 7 . To enable an ultra-high-throughput screening (uHTS) campaign, we proceeded to miniaturize both assays to 1,536 well plate format (wpf).…”
Section: Resultsmentioning
confidence: 99%
“…All data generated during this effort were uploaded to the SRMSC's institutional screening database (Assay Explorer, Symyx). Sample to background (S/B) ratios, as well as Z and Z' values, were calculated on a per-plate basis as described 7 . Curve fitting and resulting IC50 determinations were performed as previously reported 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding meprin 's precise role, alone or in combination with other metzincins, including its close relative meprin , has been difficult to establish due to the lack of known selective inhibitors. While many preliminary reports for meprin inhibitors have emerged [4][5][6][7][8] , no compounds with suitable potency, selectivity, and druglike attributes for in vivo use are known. We recently reported an HTS campaign to identify lead meprin  and meprin  inhibitors 9 .…”
Section: Introductionmentioning
confidence: 99%